A Study of Clinical and Endoscopic Profile of Acute Upper Gastrointestinal Bleeding - Dewan, KR; Patowary, BS; Bhattarai, S (Kathmandu University Medical Journal, 2015)
Backgroud Acute Upper Gastrointestinal Bleeding is a common medical emergency with a hospital mortality of approximately 10 percent. Higher mortality rate is associated with rebleeding. Rockall scoring system identifies patients at higher risk of rebleed and mortality.Objective To study the clinical and endoscopic profile of acute upper gastrointestinal bleed to know the etiology, clinical presentation, severity of bleeding and outcome.Method This is a prospective, descriptive hospital based study conducted in Gastroenterology unit of College of Medical Sciences and Teaching Hospital, Bharatpur, Nepal from January 2012 to January 2013. It included 120 patients at random presenting with manifestations of upper gastrointestinal bleed. Their clinical and endoscopic profiles were studied. Rockall scoring system was used to assess their prognosis.Result Males were predominant (75%). Age ranged from 14 to 88 years, mean being 48.76+17.19. At presentation 86 patients (71.7%) had both hematemesis and malena, 24 patients (20%) had only malena and 10 patients (8.3%) had only hematemesis. Shock was detected in 21.7%, severe anemia and high blood urea were found in 34.2% and 38.3% respectively. Upper Gastrointestinal Bleeding endoscopy revealed esophageal varices (47.5%), peptic ulcer disease (33.3%), erosive mucosal disease (11.6%), Mallory Weiss tear (4.1%) and malignancy (3.3%). Median hospital stay was 7.28+3.18 days. Comorbidities were present in 43.3%. Eighty six patients (71.7%) had Rockall score < 5 and 34 (28.3%) had >6. Five patients (4.2%) expired. Risk factors for death being massive rebleeeding, comorbidities and Rockall score >6.Conclusion Acute Upper Gastrointestinal bleeding is a medical emergency. Mortality is associated with massive bleeding, comorbidities and Rockall score >6. Urgent, appropriate hospital management definitely helps to reduce morbidity and mortality.Kathmandu University Medical Journal Vol.12(1) 2014: 21-25